Polychrome Bronze Sculpture: A Multi-Analytical Approach to Unveil the Renaissance Gilded Eagles in the Abbey of San Miniato al Monte, Florence - Emma Cantisani; Nicola Salvioli; Barbara Salvadori (Heritage, 2024)
The gilded bronze eagles that stand upon the summit of the Tabernacle by Michelozzo in the Abbey of San Miniato al Monte, Florence (Italy) are an exquisite example of Italian Renaissance sculpture. Commissioned by Piero di Cosimo de Medici, the two eagles, representing the ancient Arte di Calimala, were cast and decorated by Maso di Bartolomeo in the 1448–1449 period. A multi-analytical approach was set up to characterize the state of conservation, materials used, and artistic technique of the eagles. Non-invasive methods were used and integrated with micro-invasive analyses, such as X-ray fluorescence (XRF) and Fourier-transform infrared (FTIR) spectroscopy, X-ray diffractometry on powders (XRPD), scanning electron microscopy coupled with EDS (SEM-EDS), and metallographic investigation. The results depict shiny-looking eagles, suggesting the use of oil gilding on almost all surfaces and revealing the presence of polychromies, which is almost unusual in XV-century bronze statuary and is initially hidden by deposits and corrosion products. Indeed, the paws were originally painted with azurite, while the use of cinnabar imparted a vivid red color to the tongue. A black paint containing mercury was found on the eyes and talons. The bales of cloth were decorated with silver, which is now almost completely lost and whose remains are not visible due to being tarnished, while fine details in gold were detected on the lanyard.